Designing Better Interventions: Insights from Research on Decent Work. Issue 2 (23rd February 2021) - Hasle, Peter; Vang, Jan
Abstract : Based on our experience of carrying out theoretically and practically sound interventions to improve working conditions in global supply chains, we show what makes interventions succeed or fail and what is required to ensure that an intervention's results are sustainable in the future. Our suggestions are applicable to designing any intervention in supply chain research, but need tailoring to the local context. Our interventions were aimed at achieving decent working conditions in emerging‐country suppliers, but our insights are applicable for all supply chain scholars. In the context of emerging‐country suppliers, poor working conditions have been strongly criticized after the Rana Plaza accident and subsequently received more attention with the UN's introduction of the Sustainable Development Goals (notably, SDG 8). Tensions between productivity‐enhancing and decent work logics create challenges for the design of interventions with long‐lasting performance improvements. This paper presents a way of overcoming the tensions by illustrating how interventions that integrate improvements in working conditions with productivity can be designed.